Beirut Residents' Perspectives on August 4 Blast : Findings from a Needs and Perception Survey - World Bank (World Bank, Washington, DC, 2020)
Lebanon was rocked by an explosion at the port of Beirut on August 4, 2020 causing hundreds of deaths, wounding thousands, and leading to significant destruction of livelihoods and property. The blast occurred amid political, public health, and economic crises. As part of the immediate response, the World Bank conducted a needs and perception online survey targeting the most affected areas. The survey, deployed from August 13 to 20, 2020 captured thousands of residents’ perspectives about the explosion’s impact, their resulting needs, and their experiences with and expectations for assistance and reconstruction. The survey’s household-level results informed the preparation of the Beirut rapid damage and needs assessment, including its recommendations for the recovery and reconstruction. As the survey found that the areas hit hardest by the explosion are socioeconomically mixed, with some areas less vulnerable than others, policy and programming must balance support for those that have suffered significant losses from the immediate crisis and for those that were already experiencing deprivation. Achieving this goal requires careful coordination of aid, service provision, and reconstruction projects. Effectively capturing this data will remain necessary as perceptions of inequity and lack of transparency could fuel conflict and mistrust. Thus, attention should be given to ensure equitable distribution of assistance, particularly in reaching those most in need.